The use of the theory of planned behaviour to assess graduate attributes for sustainability. Issue 2 (1st February 2020) - Holdsworth, Sarah; Sandri, Orana; Thomas, Ian; Wong, Peter; Chester, Andrea; McLaughlin, Patricia
Abstract: Higher Education plays an influential role in societal transformation towards sustainability. An understanding of the application of sustainability learning from degree programs in a graduate's professional practice can serve as an important feedback loop for developing and advancing sustainability in higher education. A knowledge gap exists between graduate learning outcomes and employability skills, with little exploration of the methods to collect evidence of such relationships. This paper presents the results of a study to measure the uptake and application of sustainability attributes by graduates, post degree-completion. The study developed and trialled a graduate attribute assessment tool informed by the Theory of Planned Behaviour (TPB). The results demonstrate that the graduates sampled understood what was required for them to act sustainably and showed preparedness to act appropriately. However, these actions were moderated by the influence of key stakeholders and work-place contexts.